1H NMR-based metabolomics profiling and taste of stewed pork-hock in soy sauce. (July 2019) - Yang, Yi; Pan, Daodong; Sun, Yangying; Wang, Ying; Xu, Feng; Cao, Jinxuan
Abstract: Stewed pork-hock in soy sauce is a representative meat product in China. Its taste quality is highly related to primary and secondary metabolites. This study researched the effects of stewing points (0, 30, 60 and 90 min) on the metabolites profile variation of stewed pork-hock in soy sauce by using 1 H NMR spectroscopy with multivariate data analysis. The metabolome consisted of 25 metabolites, including amino acids, sugars, organic acids, nucleic acids and their derivatives. PC1 and PC2 explained a total of 90% and 7.8% of variables, respectively. Most amino acids, sucrose, β-glucose, acetate and creatinine increased during stewing, while creatine decreased. Fumarate kept extremely low content during the whole stewing process. The 60 and 90 min stewed points owned relatively higher levels of metabolites and sensory evaluation compared to other points. These results indicated that 1 H NMR-based metabolomics is useful for a better understanding on the change of meat products during the stewing process, thus improving the stewing time to provide a better taste and higher product sales of stewed pork-hock in soy sauce. Graphical abstract: Unlabelled Image Highlights: Taste is the major factor which decided by biochemical composition. The metabolites variation of stewed pork-hock in different stewing points. The proportions and combinations of metabolites explained the specific taste of stewed pork-hock in soy sauce. NMR provides detailed information on specific components of complex mixtures.